RESOLVING CONFLICT POTENTIAL: THE PREVENTIVE ACTION ON THE SHIA COMMUNITY IN YOGYAKARTA - Riza Saputra; Irza Melly; Siti Noor Aini; Ahmad Khotim Muzakka (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2020)
Since the 11th years ago the existence of the Syi'ah community in Yogyakarta lived in harmony with other groups of religions and society, however, in 2013, the leaflet is put in several places that mention